Retraction Note to: Dynamic compaction evaluation using in situ tests in Sagunto’s Harbor, Valencia (Spain) - Torrijo, Francisco Javier; Garzón-Roca, Julio; Alija, Santiago; Quinta-Ferreira, Mario (Environmental Earth Sciences, 2021)
The authors have retracted their article (Torrijo et al. 2017) because of significant overlap with previously published work (Rodriguez et al. 2015) and the masters thesis of Tomás Vicente Escrig entitled “Proyecto de mejora de rellenos hidráulicos en la explanada de la terminal de graneles sólidos en el Muelle Sur de la ampliación del Puerto de Sagunto”, which was defended in 2013 at Universidad Politécnica de Valencia.
Keywords: retraction; JCR; Scopus